Centralized assignment of prizes and contestants - Stefano Barbieri; Marco Serena (Social Choice and Welfare, 2023)
We study a contest design problem in which a designer chooses how many Tullock contests to have, how much to award to each contest, and which contestants (of high or low type) should be assigned to which contest. Our main result is that a single grand contest maximizes total effort. We consider three extensions. First, when the designers' objective changes to maximizing the effort submitted by the winning contestant, we find that the optimal design involves the high-type contestants being assigned to a set of pairwise contests. Second, under multiple participations (a player's effort is valid in multiple contests, as in several applications), running a contest open to all, along with a parallel contest open only to low types, increases total effort over a single grand contest. Third, tilting the playing field (a player's effort is multiplied by a tilting factor) in favor of low types increases total effort in a single grand contest, even more than what is possible with multiple participations; thus, in applications, a quota reserved for traditionally disadvantaged categories results in lower total effort than a grand contest that optimally handicaps advantaged categories.
Keywords: 330